Hypoglycemia and seizures associated with canine primary hepatic neuroendocrine carcinoma. (July 2021) - Dorn, Amanda R.; Brower, Alexandra; Turner, Hailey; Lapa, Klayton
A 10-y-old intact male Labrador Retriever dog had a history of ataxia, inability to stand, and grand mal seizures. Complete blood count and serum biochemistry profiles revealed profound hypoglycemia, mildly increased alanine aminotransferase (ALT) activity, mild hypernatremia, and lymphopenia. The seizures could not be controlled with intravenous dextrose, diazepam, or propofol. The dog was euthanized given poor quality of life, and an autopsy was performed. Primary autopsy findings included firm hepatic masses that ranged from dark-red to tan, with the largest ~1.5 cm diameter, and pulmonary edema. Histologic examination of the hepatic masses revealed redundant, several-cell-thick cords, and packeted or acinar arrangements of polygonal cells, supported on a fibrovascular stroma. The neoplastic cells were immunopositive for insulin, synaptophysin, and neuron-specific enolase immunohistochemistry; granules in the tumor cells had an affinity for Grimelius silver stain. The histologic features, as well as the immunohistochemical staining profile, identified the neoplasm as a primary multifocal hepatic neuroendocrine carcinoma. Neuroendocrine carcinomas are rare in dogs and usually occur in the gastrointestinal or respiratory tract.